Perancangan Aplikasi Penyedia Informasi Kerja Siswa SMK Berbasis Web Menggunakan Framework Laravel - Ori Cleoval Elia Kainde (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Vocational High School (SMK) is a level of vocational education where graduates are prepared to directly enter the world of work. An application that can provide information about workplaces was built with the aim that SMK graduates can know and prepare themselves in choosing the right place of work. This research uses Laravel technology in building a website-based application and uses the Prototyping method as a method of designing the application design. The result of this research is an application that can provide information about the workplace for SMK graduates.